A comparative study on the design of direct contact condenser for air and oxy-fuel combustion flue gas based on Callide Oxy-fuel Project. (August 2018) - Liu, Dunyu; Jin, Jing; Gao, Ming; Xiong, Zhibo; Stanger, Rohan; Wall, Terry
Highlights: A Quasi- Newton method was adopted for the rigorous design of direct contact condenser. Significance of L/G ratio on condenser height, diameter and packing volume is identified. Optimum L/G range is determined by wet bulb temperature and minimal decrease on packing volume. Capital and annual costs of DCC for air-fuel combustion are about four times and twice of these for oxy-fuel combustion. Abstract: Direct contact condenser is widely used in oxy-fuel combustion capture systems. Unusually high content of water vapor in the flue gas requires rigorous sizing procedures for the condenser design. Non-linear differential equations for humidity, gas and liquid temperatures were set up to understand the evaporation/condensation process in the condenser. A Quasi-Newton method was adopted to simultaneously solve discrete equations to avoid difficulty in convergence. This model was firstly verified with reported experiments in a packed bed condenser. The significant impacts of L/G ratio on condenser height, packing volume, condenser diameter are identified. The optimum L/G range is obtained by the wet bulb temperature and minimal decrease on packing volume, and this results in the L/G range of 2.5–5.2 and 4.3–6.7 for air and oxy-fuel combustion respectively. The condenser diameter and packing volume corresponding to the optimum L/G range for air-fuel combustion are approximately twice and four times of these for oxy-fuel combustion. While the packing height for air-fuel combustion is slightly lower than that for oxy-fuel combustion. By economic analysis, normalized total capital and annual costs for air-fuel combustion are approximately four times and twice of these for oxy-fuel combustion. The decrease of L/G ratio reduces the normalized total capital and annual costs for both air and oxy-fuel combustion and more significant for air-fuel combustion. Therefore, the L/G ratio is preferably obtained by the wet bulb temperature. This paper sheds light on the rigorous design method and the optimization of design parameters for direct contact condenser.